Little comfort [large type] - Hill, Edwin., 1970- (Hill, Edwin., 1970- Hester Thursby mystery., 2018)
A Hester Thursby Mystery In a brilliantly twisted debut set among Boston<U+2019>s elite, Edwin Hill introduces an unforgettable sleuth <U+2015> Harvard librarian Hester Thursby <U+2015> and a missing persons case that uncovers a trail of vicious murder ...